2012
DOI: 10.1100/2012/538409
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Stress Level of Children with Idiopathic Scoliosis in relation to the Method of Treatment and Parameters of the Deformity

Abstract: Stress level due to existing body deformity as well as to the treatment with a corrective brace is one of factors influencing the quality of life of children with idiopathic scoliosis undergoing non-surgical management. The purpose of the study was to evaluate the stress level among children suffering from idiopathic scoliosis in relation to the method of treatment and the parameters of the deformity. Seventy-three patients with idiopathic scoliosis participated in the study. Fifty-two children were treated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 20 publications
0
15
0
7
Order By: Relevance
“…In spite of the continuous improvement of this method by modernizing braces and improving their aesthetic aspects, it still exerts a considerable influence on the life of the patient and his family [8.11-14,17]. As some studies have shown, the stress that patients experience during treatment may be related to brace-wearing more than to the presence of torso deformities [18]. This is especially clearly visible in children during puberty when they more frequently pay attention to their external appearance as they seek acceptance in the peer group [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the continuous improvement of this method by modernizing braces and improving their aesthetic aspects, it still exerts a considerable influence on the life of the patient and his family [8.11-14,17]. As some studies have shown, the stress that patients experience during treatment may be related to brace-wearing more than to the presence of torso deformities [18]. This is especially clearly visible in children during puberty when they more frequently pay attention to their external appearance as they seek acceptance in the peer group [10].…”
Section: Discussionmentioning
confidence: 99%
“…Po mi mo cią głe go udo sko na la nia tej me to dy przez uno wo cze śnia nie i po pra wę es te ty ki gor se tów na dal wy wie ra ona du ży wpływ na ży cie pa cjen ta, a ta kże je go ro dzi ny [8,[11][12][13][14]17]. Jak po ka zu ją nie któ re bada nia, stres ja ki pa cjen ci od czu wa ją w trak cie le czenia mo że być w więk szym stop niu zwią za ny z faktem no sze nia gor se tu or to pe dycz ne go, niż z obec nością de for ma cji tu ło wia [18]. Jest to szcze gól nie widocz nie u dzie ci w okre sie doj rze wa nia, kie dy co raz czę ściej i w więk szym stop niu przy wią zu ją one uwagę do swo je go wy glą du ze wnętrz ne go, a ta kże poszu ku ją ak cep ta cji w gru pie ró wie śni czej [10].…”
Section: Dys Ku Sjaunclassified
“…В клинико-психологических исследованиях отечественных авторов рассматриваются преимущественно психологические проблемы больных со спинальными травмами [4][5][6], с врожденными формами сколиоза [5,6]. Психологические особенности больных с AIS представлены в основном в работах зарубежных исследователей [7][8][9][10][11][12][13][14][15][16][17][18][19][20] и в отдельных работах отечественных авторов [21][22][23][24][25].…”
Section: анализ проблемыunclassified
“…В данных исследованиях получены противоречивые данные. Результаты одних исследований показывают, что параметры качества жизни у подростков с идиопатическим сколиозом снижены [43], а в других исследованиях отмечается средне-вы-сокий уровень качества жизни [19]. Авторы выделяют клинические характеристики, которые могут влиять на качество жизни: зрелость скелетной мускулатуры, особенности искривления позвоночника, характер лечебных мероприятий, длительность ношения корсета [11].…”
Section: анализ публикаций по идиопатическому сколиозуunclassified
“…The IS can affect the social sphere, limiting job opportunities, social isolation and lower marriage rates (7), moreover interferes negatively on self image (8,9) and stress level (10). IS progression can result in back pain, reduced mobility and lung function (11), postural stability deficit (12 -14), muscle force imbalance (15,16), altered electromyographic activity (17), increased risk of lumbar and thoracic pain and degenerative diseases of the intervertebral disc (18,19).…”
Section: Introductionmentioning
confidence: 99%